Testability Research of Civil Aircraft Cockpit Lighting System - Shihui, Chen (IEEE ... Information Technology and Mechatronics Engineering Conference (ITOEC ... ) (Online), 2025)
The cockpit lighting system is a critical human-machine interface that integrates controls, displays, and lighting for status control and indication across various aircraft systems. It enables flight crews to operate aircraft systems and provides illumination and status displays under all cockpit lighting conditions. Effective cockpit lighting design mitigates pilot visual fatigue, enhances operational accuracy, and reduces the risk of human error-induced flight accidents, thus fostering a more comfortable flight environment. Adhering to MIL-STD-2165, this study employs diverse testability design and analysis methods, including FMEA, testability analysis, and BIT design, to enhance the testability and safety of the cockpit lighting system. The research contributes novel perspectives and methodologies for the design and maintenance of future civil aircraft cockpit lighting systems, emphasizing fault detection and prediction to ensure system reliability throughout its lifecycle.